Análise da correspondência entre Manuel Bandeira e Ribeiro Couto - Casagrande, Rosângela Fonseca (2006)
This study has as objective showing the importance of the letters, as influence in the process of the literary creation of Manuel Bandeira and Ribeiro Couto, in view of the second phase of the modernist movement, in the period between 1929 and 1939. At the same time, I want to demonstrate that the referring poetical function to the letters as literary genre, allows, many times, an aesthetic enjoyment. Under this subject, Sophia Angelides, in Carta e Literature (apud SCHNAIDERMAN, 2001, p.23-24), affirms : "in the personal testimonials of a writer, the poetical function can manifest itself with greater or minor intensity, but, in someway, the speech is marked by a peculiar procedure that will allow, many times, the aesthetic enjoyment". This way for Angelides "the proper spontaneous and fragmentary character, the alternation of the poetical and not poetical language, the cliches, everything is inherent to the epistolar genre. Being this way, many of the letters changed between Manuel Bandeira and Ribeiro Couto assume didactic value, others correspond to the intensity of feelings, transforming themselves into a subjective artistic expression that favors the understanding of the workmanships. The literary subjects in the letters are these: references to the workmanships published for both, appreciation of these workmanships, including citation of chronicles and quarrel of genres. Still, the letters exchanged between the two poets disclose tboth of theirs opinions on painting, the poetry of Carlos Drummond de Andrade, Jorge de Lima, Múcio Leão, etc. This way, the correspondence between Manuel Bandeira and Ribeiro Couto supplies information to us on the intellectual and literary trajectory of both, giving a theoretical and utilitarian contribution to the study of the genres in Brazilian Literature, in particular, the epistolar one